2011
DOI: 10.1080/01973533.2011.589294
|View full text |Cite
|
Sign up to set email alerts
|

Judgments of Sexual Abuse Victims

Abstract: Three experiments address how people react to a sexual abuse victim compared to a nonvictim when a justification for negative evaluation is available or not available. A harm-doing victim was rated lower on expected job performance and higher on desired social distance than a harm-doing nonvictim. When subsequent harm-doing was absent, judgments of a victim and nonvictim did not differ on expected job performance or social distance. Experiment 2 replicated the results of Experiment 1 and revealed that the orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…For example, perceivers viewed a victim of a tragedy as more likely to have a meaningful and enjoyable life than a nonvictim when under high justice threat compared with low justice threat (Anderson et al, 2010). In addition, observers believed that a victim of childhood sexual abuse should grow up to become a more ethical and kinder person than a nonvictim (Warner, Branscombe, Garczynski, & Solomon, 2011). These findings are consistent with just world theory's assertion that perceiving an individual victim as becoming a better person and believing that the victim should become more prosocial is one strategy for making meaning of injustice.…”
Section: The Meaning Of Historical Victimization For Observersmentioning
confidence: 99%
“…For example, perceivers viewed a victim of a tragedy as more likely to have a meaningful and enjoyable life than a nonvictim when under high justice threat compared with low justice threat (Anderson et al, 2010). In addition, observers believed that a victim of childhood sexual abuse should grow up to become a more ethical and kinder person than a nonvictim (Warner, Branscombe, Garczynski, & Solomon, 2011). These findings are consistent with just world theory's assertion that perceiving an individual victim as becoming a better person and believing that the victim should become more prosocial is one strategy for making meaning of injustice.…”
Section: The Meaning Of Historical Victimization For Observersmentioning
confidence: 99%
“…To the extent that Indigenous peoples are successful in conveying their strengths and their inherent right to equity, respect and self-determination, any violation of the moral expectations placed upon them could come at a high social cost [ 3 , 35 ]. Specifically, although victim blame was not assessed, highlighting the strengths of Indigenous peoples could potentially lead to the belief that the conditions they have faced and continue to face are of their own doing.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Branscombe et al (2015) found that when members of a historically victimized group (the descendants of holocaust survivors) violated these perceived moral obligations by harming others, they were viewed more negatively than were non-victims (or even the historical perpetrators of the victimization of the focus group) who engaged in the same harmful behaviour. Similarly, when individual victims (childhood abuse survivors) violated moral expectations by harming others, observers viewed these individuals as comparatively less competent (measured in terms of expected job performance) and desired greater social distance than they expressed toward the original perpetrators (i.e., the abusers) who engaged in the same harm-doing behaviour (Warner, Branscombe, Garczynski, & Solomon, 2011).…”
Section: Perceptions Of Indigenous Moral Obligationsmentioning
confidence: 99%
“…In turn, the degree to which an observer expects that an individual's or a group's victimization should have yielded positive benefits (e.g., improvements to their strength of character) is predictive of the degree to which the observer imposes moral obligations onto the victim or victim group (Warner & Branscombe, 2010). It has been suggested that if an observer believes that the victimization of a person or group has yielded positive consequences, these benefits are expected to manifest themselves in greater morality, and greater social distance from victims who fail to meet that greater moral bar is desired (Warner et al, 2011).…”
Section: Perceptions Of Indigenous Moral Obligationsmentioning
confidence: 99%